Reconciling qualitative, abstract, and scalable modeling of biological networks - Loïc Paulevé (Nature Portfolio, 2020)
Boolean Networks are a well-established model of biological networks, but usual interpretations can preclude the prediction of behaviours observed in quantitative systems. The authors introduce Most Permissive Boolean Networks, which are shown not to miss any behaviour achievable by the corresponding quantitative model.